Measurement of Bmax and Kd with the Glycine Transporter 1 Radiotracer 18F-MK6577 using a Novel Multi-Infusion Paradigm. Issue 12 (December 2015) - Xia, Yan; Zheng, Ming-Qiang; Holden, Daniel; Lin, Shu-fei; Kapinos, Michael; Ropchan, Jim; Gallezot, Jean-Dominique; Huang, Yiyun; Carson, Richard E
Glycine is a co-agonist of glutamate at the NMDA receptor. Glycine transporter 1 (GlyT1) inhibitors are reported to be potential therapeutic agents for schizophrenia. 18 F-MK6577 is a new positron emission tomography (PET) radiotracer useful for imaging brain GlyT1 and its occupancy in humans. We devised a novel multi-infusion paradigm of radiolabeled and unlabeled compound and an iterative linear/nonlinear alternating fitting method to allow for the determination of in vivo affinity ( K d ) and target concentration ( B max ) images, constraining K d to be uniform across the brain. This paradigm was tested with 18 F-MK6577 in baboons. Voxel-based analysis produced high quality B max images and reliable K d estimates, and also suggested that the nondisplaceable distribution volume ( V ND ) is not uniform throughout the brain. In vivo GlyT1 K d was estimated to be 1.87 nmol/L for 18 F-MK6577, and the rank order of GlyT1 distribution measured in the baboon brain was: high in the brainstem (133 nmol/L), medium in the cerebellum (83 nmol/L), and low in the cortex (30 nmol/L). These in vivo K d and B max values agreed well with those determined in vitro, thus validating our novel multi-infusion approach.